2010
DOI: 10.1210/er.2009-0026
|View full text |Cite
|
Sign up to set email alerts
|

The Secret Life of NAD+: An Old Metabolite Controlling New Metabolic Signaling Pathways

Abstract: A century after the identification of a coenzymatic activity for NAD(+), NAD(+) metabolism has come into the spotlight again due to the potential therapeutic relevance of a set of enzymes whose activity is tightly regulated by the balance between the oxidized and reduced forms of this metabolite. In fact, the actions of NAD(+) have been extended from being an oxidoreductase cofactor for single enzymatic activities to acting as substrate for a wide range of proteins. These include NAD(+)-dependent protein deace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
866
1
9

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 784 publications
(891 citation statements)
references
References 245 publications
(190 reference statements)
15
866
1
9
Order By: Relevance
“…These enzymes were found to play important roles in cellular signaling related to cell death, Ca 2+ homeostasis, and lifespan extension, and their activities are highly dependent on the level of NAD + available in the cell (4,5,8,9,33,41,42). In this study, other than the decreases in the intracellular NAD + level and RX (or RP), we also observed a slower decline of the total intracellular NAD content in the human brain during healthy aging, which collectively reflects reduced NAD + availability in the aged brain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These enzymes were found to play important roles in cellular signaling related to cell death, Ca 2+ homeostasis, and lifespan extension, and their activities are highly dependent on the level of NAD + available in the cell (4,5,8,9,33,41,42). In this study, other than the decreases in the intracellular NAD + level and RX (or RP), we also observed a slower decline of the total intracellular NAD content in the human brain during healthy aging, which collectively reflects reduced NAD + availability in the aged brain.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that, by supplying NAD + precursors or intermediates and/or introducing PARPs or CD38 inhibitor, one could enhance the NAD + biosynthesis and/or inhibit its consumption, thus boosting the intracellular NAD + level (6,10,11,43). Such interventions are suggested to promote therapeutic effects of lifespan extension and neuroprotection and could potentially be used with other physiological managements, such as calorie restriction, fasting, or exercise, to compensate for the natural decline of brain NAD + in normal aging and prevent or treat age-related metabolic disorders (3,4,33,44,45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to its role in redox metabolism, proteins such as the sirtuins are regulated by, and consume, NAD ϩ , allowing them to act as metabolic sensors that can regulate downstream metabolic pathways (19). Metabolites of NAD ϩ that result from these enzymatic reactions potently mobilize intracellular Ca 2ϩ stores by acting directly on ryanodine receptors (20) as well as unidentified receptors in other compartments (21) and activate Ca 2ϩ influx carried by TRPM2 channels (22).…”
mentioning
confidence: 99%
“…In case of the hydrolyzing of NAD + and transferring of the lysine‐bound acetyl group, the loop was moved, and the binding site was blocked, followed by activator release and deacetylated product dissociation. On the other hand, the hydrolyzed product of NAD + was nicotinamide (NAM), and the transferred product of the lysine‐bound acetyl group was 2′‐O‐acetyl adenosine diphosphate(ADP)‐ribose; NAM was transferred to nicotinamide mononucleotide(NMN) by nicotinamide phosphoribosyl transferase (NAMPT), and then the NMN was transferred back to NAD + by nicotinamide mononucleotide adenylyltransferase (NMNAT), forming the NAD + cycle 22, 23. The above results indicated that NaB could contribute to the stabilization of the Sirt3/substrate complex by ordering the “adaptable loop”, leading to the deacetylation of the enzyme for the substrate through stabilized exposure to the “active site”.…”
Section: Resultsmentioning
confidence: 99%